799 Factors Influencing Early Neonatal Mortality in Retrieved Extreme Preterm Neonates. (October 2012) - Wilson, K; Nagy, A; Green, C; Boyd, D; Ratnavel, N; Mohinuddin, S
Abstract : Background and Aims: Neonatal care is increasingly delivered within regionalised networks, often necessitating transfer of vulnerable preterm babies from local neonatal units to neonatal intensive care units (NICU). Extreme preterm infants (gestation < 28 weeks) born in hospitals without a NICU have a relatively higher mortality rate than those inborn in hospitals with NICU. In this study we aim to investigate the factors that impact on early (7-day) neonatal mortality in retrieved extreme preterm infants. Methods: Inclusion criteria (< 28 weeks gestation, transfer < 24 hours of birth, complete data entry) were applied to all entries in a regional transfer service database between January 2005 and December 2011 (n=7669) leaving 621. Early mortality was analysed against gestational age, birth weight, lowest pH, temperatures on NTS arrival at referring unit (T1), departure from referring unit (T2) and arrival at the receiving unit (T3). Statistical analysis was carried out using SPSS v18. Results: 7-day mortality was 88 (14.17%). Mean (Range) for gestational age was 25.35 weeks (22.0–27.86), birth weight 794g (440–1650) and lowest pH (prior to transfer) was 7.28 (6.90–7.53). Only gestational age (< 0.001), birth weight (p<0.001) and lowest pH affected mortality individually (p<0.001). Mortality was not significantly affected by T1 (p=0.152), T2 (p=0.265) and T3 (p=0.065). To control for confounding, we performed logistic regression, after which gestational age (p<0.001) and lowest pH (p=0.001) remained significant. Conclusion: Gestational age and lowest pH significantly influence 7-day mortality within retrieved extreme preterm infants.